Mucoadhesive, Thermoreversible Hydrogel, Containing Tetracaine-Loaded Nanostructured Lipid Carriers for Topical, Intranasal Needle-Free Anesthesia - Giovana Maria Fioramonti Calixto; Bruno Vilela Muniz; Simone R. Castro; Jaiza Samara Macena de Araujo; Klinger de Souza Amorim; Lígia N. M. Ribeiro; Luiz Eduardo Nunes Ferreira; Daniele Ribeiro de Araújo; Eneida de Paula; Michelle Franz-Montan (MDPI AG, 2021)
Recent advances have been reported for needle-free local anesthesia in maxillary teeth by administering a nasal spray of tetracaine (TTC) and oxymetazoline, without causing pain, fear, and stress. This work aimed to assess whether a TTC-loaded hybrid system could reduce cytotoxicity, promote sustained permeation, and increase the anesthetic efficacy of TTC for safe, effective, painless, and prolonged analgesia of the maxillary teeth in dental procedures. The hybrid system based on TTC (4%) encapsulated in nanostructured lipid carriers (NLC) and incorporated into a thermoreversible hydrogel of poloxamer 407 (TTCNLC-HG4%) displayed desirable rheological, mechanical, and mucoadhesive properties for topical application in the nasal cavity. Compared to control formulations, the use of TTCNLC-HG4% slowed in vitro permeation of the anesthetic across the nasal mucosa, maintained cytotoxicity against neuroblastoma cells, and provided a three-fold increase in analgesia duration, as observed using the tail-flick test in mice. The results obtained here open up perspectives for future clinical evaluation of the thermoreversible hybrid hydrogel, which contains TTC-loaded NLC, with the aim of creating an effective, topical, intranasal, needle-free anesthesia for use in dentistry.